The role of new civil society organizations in promoting sexual health in Chile - Obach, Alexandra; Sadler, Michelle; Marín, Matías (Revista de Antropología Social, 2023)
The article −which gives an account of the results of two qualitative investigations carried out between 2020 and 2022−, has the purpose, from a global health, collective health and structural vulnerability approach, to reflect on the role played by new civil society actors in the promotion of sexual health, sexual rights and in the prevention and detection of HIV in Chile. These actors are civil society organizations led by young health professionals who have built spaces for information, promotion, and care in sexual and reproductive health outside the formal health system; and organizations led by LGBTIQA+ youth around information on sexualities in general, and access to HIV prevention and detection in particular. The article contributes to show the importance that these new civil society actors have in therapeutic trajectories in the field of sexual health of young people in Chile, and the even greater relevance that they have acquired since the beginning of the Covid-19 pandemic.